A Problem-based Approach for Management Education - Hallinger, Philip. author. aut Link
XVIII, 326 p.
Keywords: The past two decades have witnessed an unrelenting expansion of management education around the world. At the same time, however, influential scholars – Mintzberg, Bennis, Pfeffer and others -- have levelled pointed critiques at these programs questioning their quality and relevance, as well as their approaches to teaching and learning . ‘A Problem-based Approach for Management Education" is a timely contribution for management schools as well as other higher education institutions seeking the means to increase the relevance and quality of their professional education programs. The book describes the use of problem-based learning (PBL) in GRADUATE management education. PBL is an active learning approach first pioneered in medical education, but whose use has grown steadily in a variety of professional fields over the past two decades. This volume is the first of its kind targetting business management. The authors draw upon their experience in using PBL in a broad array of management education programs at the Bachelor, Master, Doctoral and Executive levels, in North America and in Asia. They propose PBL as a means by which programs can organize an increasingly global MBA curriculum around locally relevant management problems. The book should have a particularly strong appeal for programs in the Asia Pacific region given the inclusion of PBL. Materials developed around management problems in Asia. This book is designed to provide both novice and experienced users of PBL with resources for designing and implementing problem-based management education. The book provides the novice with useful theoretical and practical background on how to design a PBL curriculum, use PBL in a classroom, and develop PBL materials. At the same time, the book will challenge experienced users of PBL and case teaching to extend their applications through the use of learning technologies and more systematic approaches to assessment andcurriculum design. Finally, the volume includes a set of sample PBL materials that provide readers with in-dept examples of what a PBL unit looks like and how it may be employed in the classroom.